Integrative and complementary practices: challenges in implementation in the Single Health System (Research, Society and Development, 2022)
Objective: to analyze the scientific productions about the challenges of implementing integrative and complementary practices (PICS) in the unified health system. Methodology: this is an integrative review of the literature registered in the SciElo and LILACS databases using the descriptors “integrative and complementary practices”, “unified health system” and “public health” and which met the following inclusion criteria: text available free of charge in national and international journals and published between 2011 and 2021. Editorials, letters to the editor, experience reports, reflective studies and state of the art were excluded from this review. Results: after applying the established criteria, 08 studies were selected for this review. From the analysis of the articles, three categories emerged: lack of knowledge about the national policy of integrative and complementary practices; Professional training to work with the PICs; Approach to PICs during graduation. Conclusion: the lack of information both by professionals who practice and by the public that enjoys it, compromises the effectiveness of practices and the full use of these forms of maintenance in the quality of life. In addition, it is important that management commits to implementing PICs in the SUS, in order to promote comprehensive care.